A critique of the expression of paediatric body composition data. Issue 1 (1st July 2001) - Wells, J C K
Abstract : There is increasing interest in body composition in paediatric research, as distinct from growth and nutritional status, as almost all diseases have adverse effects on either fatness or the fat-free mass. However, the approaches used to assess growth and nutritional status are not appropriate for separate evaluations of body fatness and lean mass. Traditional measurements such as body mass index and skinfold thickness do not measure fat in accurate quantitative terms. Various techniques have been used in recent years which divide body weight into fat mass and fat-free mass; however, the data tend not to be appropriately expressed. Body fatness is generally expressed as a percentage of weight, while fat-free mass typically remains unadjusted for size. A more appropriate approach is to normalise both body fatness and fat-free mass for height. This recommendation is relevant both to studies comparing patients with controls and to the expression of new reference data on body composition which are needed to allow informative comparisons. The same approach is appropriate for the classification of childhood obesity.